Integrative review: Mental health interventions with healthcare professionals in the hospital settings - Forni dos Santos, Larissa (2025)
Healthcare professionals are exposed to various work conditions that can affect their mental health. Starting from the following question: “what interventions have been conducted in the field of mental health for healthcare teams working in a hospital context?”, we conducted an integrative review covering the period from 2001 to 2022, using the databases PubMed, Web of Science, Scopus, and Biblioteca Virtual em Saúde (BSV). Nine original studies with different methodological designs were included. Several variables were analyzed, including stress, burnout, job satisfaction, depression, anxiety, resilience, well-being, and quality of life, among others. Except for job satisfaction and self-efficacy, the remaining variables showed positive results.